Excitation-Independent Deep-Blue Emitting Carbon Dots With 62% Emission Quantum Efficiency and Monoexponential Decay Profile for High-Resolution Fingerprint Identification - Savaedi, Soheyla; Soheyli, Ehsan; Zheng, Guangsong; Lou, Qing; Sahraei, Reza; Shan, Chongxin (IOP Publishing Ltd, 2022)
Reaching emissive nanomaterials at short wavelengths with a high quantum efficiency (QE) is an attractive task for researchers. This is more demanding in carbon dots (CDs) with diverse applications that usually emit photons at wavelengths around 450-620 nm. In this study, deep blue-emissive doped-CDs (d-CDs) with high photoluminescence (PL) QE up to 62% and excitation-independent properties were prepared via a short-time microwave irradiation method. The prepared CDs showed simultaneous amorphous and crystalline features, with average sizes of 4.75 nm and bright emission color located at 422 nm. It was found that the presence of sulfur-related dopant levels plays a key role in emission properties in such a way that the PL signal drops significantly in the absence of N-acetyl-l-cysteine (NAC) as a dopant source. On the other hand, the trisodium citrate dihydrate (TSC) was selected as a carbon source to form the main carbon skeleton without it no emission was recorded. Monoexponential-fitted recombination trend with an average lifetime of about 10 ns also confirmed excellent PL emission properties with uniform energy levels and minimized defect-contributing recombinations. The practical use of the as-prepared N, S-doped CDs was assessed in fingerprint detection indicating a bright and clear scheme for both core and termination regions of the fingerprint. Simplicity, cost-effectiveness, high-product yield, low toxicity, along with high/stable PL quantum efficiency in deep-blue wavelengths, and demonstrated ability for fingerprint purposes, support the prospective application of these dual doped-CDs for sensing and bioimaging applications.
Lou, Qing/0000-0002-8852-8453; Soheyli, Ehsan/0000-0002-1403-7934; Sahraei, Reza/0000-0001-7104-2126
Keywords: Carbon Dots; Deep-Blue Emission; High Emission Yield; Single-Exponential Decay; Fingerprint